Resilience of agri-food system in the EU context: Pandemic crisis lessons and sectoral overview - Mirela Rusali (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
Covid-19 crisis have revealed the most fragile social and economic aspects worldwide while confronting this overpowering collective challenge, yet having more impact on zones already vulnerable before pandemic broke in the first wave. Covidemia affected the agricultural sector in EU in the extent that it was already challenged by other threats regarding production, or other causing market uncertainties. Moreover, inequalities in access to food have been probable aggravated. The main lesson the pandemic might have given to people and policy makers so far is that health and life are of paramount importance. Still, effects on the global food system were perceived as a distress on food security worldwide, with market closures, supply disruptions, and losses of employment and income. The purpose of the paper stands in understanding the extent and nature of these impacts is essential to building resilience to future shocks. The research contains a synthesis of main impacts of pandemic crisis on agri-food value chain and reactions in EU, following a stocktaking of recent studies and reports provided online; as well, an overview on the state of Romania's manufacturing agri-food sectors in the EU context, based on economic indicators of food manufacturing enterprises, using the most recent statistics from Eurostat and NIS. The results revealed certain gaps and vulnerabilities, underpinning the further needs for targeted policies towards supporting the national food industry resilience as the major driver of socio-economic security, within crisis and post-crisis, as a basis of sustainable agri-food system.
Keywords: Q13; L66; F6; 330; agri-food system; manufacturing enterprises; resilience